(untitled) (Journal of Scientific Research, 2011)
The sodium-calcium exchange (NCX) is one of the major regulators of intracellular Ca2+ concentration in cardiac myocytes. The effects of NCX blockers as antiarrhythmic agents are still controversial. We investigated antiarrhythmic effects of SEA0400 (SEA), a novel NCX inhibitor, on ouabain-induced arrhythmias in guinea pigs. In the whole animal arrhythmia model, we observed effects of SEA on the ouabain-induced arrhythmia using ECG recordings. In the isolated myocyte, we observed action potential configurations and oscillations due to calcium overload using the current clamp method. In the whole animal model, SEA at a dose range of 1-10 mg/kg (intravenous, bolus) suppressed ouabain-induced arrhythmias dose-dependently. In isolated ventricular myocytes, SEA (0.1-3 µM) suppressed ouabain-induced oscillatory activity observed between action potentials. SEA (0.1-3 µM) also suppressed ouabain-induced NCX current (INCX) that is also called transient inward current (ITI). Our results indicate that NCX is involved in arrhythmia and oscillatory activity induced by ouabain. The inhibition of these arrhythmias and oscillatory activity by SEA might result from the inhibition of NCX. Keywords: Na+-Ca2+ exchange (NCX); SEA0400; NCX inhibitors; current clamp; ECG. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i1.7722 J. Sci. Res. 4 (1), 213-225 (2012)